Loss distribution and characterization of MMC sub‐modules for HVDC applications. (3rd August 2021) - Tian, Yumeng; Wickramasinghe, Harith R.; Pou, Josep; Konstantinou, Georgios
Summary: The losses and efficiency of a modular multilevel converter (MMC) are strongly linked to the switching frequency, component selection, and the choice of internal control structures such as the circulating current control and sub‐module (SM) capacitor voltage balancing algorithm. Equally, the structure of the SM impacts the overall converter operation and the efficiency of the conversion system. However, consideration for the impact of converter operating points on the overall system efficiency is required in order to derive a complete picture. Thus, this paper presents a comprehensive evaluation of the impact of inverter/rectifier operation and power factor on the losses of the different SMs in an MMC with a particular focus on SMs and operational limits for high‐voltage DC transmission systems. Considering 27 different SM topologies, it is demonstrated that due to the voltage balancing requirements, the inverter or rectifier operation modes of the converter and the power factor, influence the average losses of SMs and also the maximum and minimum losses within a fundamental period. Abstract : An analysis of the impact of the power factor angle and a comparison between the minimum, maximum, and average losses in different MMC SMs in HVDC applications. The structure of the SM affects the losses, with variations on the losses of the same SM in rectifier and inverter operation and different power factors. The results can be used in applications beyond HVDC systems and for other cascaded multilevel converters.